Tm3+/Cr3+ Codoped Dual‐Phase Transparent Glass‐Ceramics for Light Conversion in Photosynthesis. Issue 3 (4th February 2021) - Chen, Qinpeng; Cai, Zhenlu; Pan, Qiwen; Dong, Guoping
Abstract : To improve the utilization efficiency of chlorophyll to sunlight, Tm 3+ /Cr 3+ codoped dual‐phase glass‐ceramics are successfully fabricated as a dual‐light conversion material by the conventional melt‐quenching technique with subsequent heat treatment. Exploiting the radius difference in atomic size, Tm 3+ and Cr 3+ ions have been rationally designed entering into the NaYF4 and NaAlSiO4 crystal phase, respectively, to avoid detrimental energy quenching. The resulted dual‐phase glass‐ceramics exhibit a great emission enhancement compared to the precursor glass. No obvious lifetime degradation in the codoped glass‐ceramic further proves the successful incorporation of Tm 3+ and Cr 3+ in distinguished crystalline phases. Utilizing the dual‐phase glass‐ceramics, the useless sunlight can be converted into the desired red/blue region and reabsorbed by the chlorophyll. The Tm 3+ ions convert ultraviolet light into the blue region, and the Cr 3+ ions transfer green light to the red emission. With the utilization of Tm 3+ /Cr 3+ codoped dual‐phase glass‐ceramics in the greenhouse, the photosynthesis process can be promoted, and furthermore, the production of crops can be improved, indicating the potential applications in the field of green agriculture. Abstract : To improve the utilization efficiency of chlorophyll to sunlight, Tm 3+ /Cr 3+ codoped dual‐phase glass‐ceramics are successfully fabricated as a dual‐light conversion material. Utilizing the dual‐phase glass‐ceramics, the Tm 3+ ions convert ultraviolet light into the blue region, and Cr 3+ ions transfer green light to the red emission, which can be reabsorbed by the chlorophyll.